Functional Outcomes in Survivors of Pediatric Sepsis: A Scoping Review and Discussion of Implications for Low- and Middle-Income Countries - Ravikumar, Namita; Sankar, Jhuma; Das, Rashmi Ranjan (Frontiers in Pediatrics, 2022)
Background: Pediatric sepsis is an important cause of mortality and morbidity in low- and middle-income countries (LMIC), where there is a huge burden of infectious diseases. Despite shortage of resources, adapting protocol based care has reduced sepsis related deaths but survivors of pediatric sepsis are at risk of poor functional outcomes. Objectives: To perform a scoping review of the literature on functional outcomes of pediatric sepsis survivors after discharge from the intensive care unit (ICU) and discuss the implications for patients in LMICs. The outcomes include prevalence of survival with reduced functional outcomes or quality of life (QoL), changes over time during follow-up or recovery, and to compare these outcomes with other groups of children. Methods: We searched major medical electronic databases for relevant literature from January 2005 till November 2021, including Medline (via PubMed), Embase, CINAHL, and Google scholar databases. We included observational studies and follow-up data from clinical trials involving children/adolescents (¬¬≤18 years) who were admitted to pediatric intensive care unit (PICU) and got discharged finally. Major focus was on survivors of sepsis in LMIC. We followed PRISMA guideline for scoping reviews (PRISM-ScR). Results: We included eight papers reporting data of functional outcomes in 2,915 children (males = 53%, and co-morbidity present in 56.6%). All included studies were either prospective or retrospective cohort study. Studies were classified as Level II evidence. Disabilities affecting physical, cognitive, psychological and social function were reported in children following discharge. Overall disability reported ranged between 23 to 50% at hospital discharge or 28 days. Residual disability was reported at 1, 3, 6 and 12 month of follow up with an overall improving trend. Failure to recover from a baseline HRQL on follow up was seen in one-third of survivors. Organ dysfunction scores such as pSOFA, PeLOD, vasoactive inotropes score, neurological events, immunocompromised status, need for CPR and ECMO were associated with poor functional outcome. Conclusions: The research on functional outcomes in pediatric sepsis survivors is scarce in LMIC. Measuring baseline and follow-up functional status, low-cost interventions to improve management of sepsis, multi-disciplinary teams to identify and treat disabilities may improve functional outcomes.